Transforming Higher Education through NEP 2020: An Analysis of Challenges and Opportunities (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Sudesh KumariAn explicit and futuristic education policy is essential for any country, not only at the school level, but also at higher levels. The National Education Policy (NEP) 2020 represents a paradigmatic shift in India's higher education, and it is focused on five pillars: Accessibility, Equality, Affordability, Quality, and Accountability. These pillars collectively aim to create an ecosystem of continuous learning opportunities that transcends traditional educational boundaries.This paper examines the transformative impact of NEP 2020 on higher education. Key findings reveal that NEP 2020 envisions a strategic consolidation of India's higher education landscape into three distinct institutional categories, designed to significantly enhance the Gross Enrollment Ratio (GER). This restructuring has already begun yielding results. India's GER has witnessed a remarkable journey from 23.7% in 2014-15 to 28.4% in 2021-22, translating to an enrollment surge from 3.42 crore to 4.33 crore students.